2022
DOI: 10.3389/fchem.2022.1040435
|View full text |Cite|
|
Sign up to set email alerts
|

How β-cyclodextrin- loaded mesoporous SiO2 nanospheres ensure efficient adsorption of rifampicin

Abstract: In this study, β-CD@mesoporous SiO2 nanospheres (β-CD@mSi) were prepared by loading β-cyclodextrin (β-CD) onto mesoporous silica nanospheres through an in situ synthesis. This not only solved the defect of β-CD being easily soluble in water, but also changed the physical structure of the mesoporous silica nanospheres. FTIR and XPS results showed that β-CD was successfully loaded onto mesoporous silica nanospheres (mSi), while enhancing the adsorption effect. β-CD@mSi with a monomer diameter of about 150 nm wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The nano-SiO 2 spheres were first synthesized as follows: 0.999 g of CTAB was dissolved in 480 mL of distilled water, and 3.5 mL of NaOH (2 mol/L) solution was added to the above solution. The mixed solution was put in an 80 °C oil bath and stirred continuously for 10 min.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The nano-SiO 2 spheres were first synthesized as follows: 0.999 g of CTAB was dissolved in 480 mL of distilled water, and 3.5 mL of NaOH (2 mol/L) solution was added to the above solution. The mixed solution was put in an 80 °C oil bath and stirred continuously for 10 min.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Since the ΔG value is negative, and the ΔS value is positive, it may be concluded that the RIF adsorption is a spontaneous and disordered process. The kinetic data can be tted to the pseudo-rst-order and pseudo-second-order models described by equations ( 8) and (9), respectively [37,38]: 8 9 where q t (mg/g) and q e (mg/g) are the adsorption capacity values at time t (min) and at equilibrium, respectively; k 1 (L/min) and k 2 (g/(mg•min)) are the constants for the pseudo-rst-order and pseudosecond-order models, respectively.…”
Section: Adsorption Isotherms and Thermodynamicsmentioning
confidence: 99%